2022
DOI: 10.1002/chem.202200850
|View full text |Cite
|
Sign up to set email alerts
|

When Aggregation‐Induced Emission Meets Perovskites: Efficient Defect‐Passivation and Charge‐Transfer for Ambient Fabrication of Perovskite Solar Cells

Abstract: The intrinsic defects in perovskite film can serve as non‐radiative recombination center to limit the performance and stability of metal halide perovskite solar cells (PSCs). The additive engineering in perovskite film is always applied to produce high‐efficiency PSCs in recent years. Here, a typical donor‐acceptor (D−A) structured aggregation‐induced emission (AIE) molecule tetraphenylethene‐2‐dicyano‐methylene‐3‐cyano‐4,5,5‐trimethyl‐2,5‐dihydrofuran (TPE‐TCF) was introduced into perovskite film. The D−A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Besides outstanding photovoltaic performance, the shelf stability under harsh operating conditions is still another bottleneck in the direction of the large-scale commercial application of PSCs . All the numerous GBs, interfacial nonradiative recombination, and charge accumulation have been widely recognized to induce the degeneration of perovskite materials .…”
Section: Resultsmentioning
confidence: 99%
“…Besides outstanding photovoltaic performance, the shelf stability under harsh operating conditions is still another bottleneck in the direction of the large-scale commercial application of PSCs . All the numerous GBs, interfacial nonradiative recombination, and charge accumulation have been widely recognized to induce the degeneration of perovskite materials .…”
Section: Resultsmentioning
confidence: 99%
“…The planar heterojunction PSCs were fabricated according to our previous work. 20,21 The FTO glass substrates were cleaned by ultrasonication in acetone and absolute ethanol, each for 15 min. Then, the substrates were pre-cleaned with isopropanol (IPA).…”
Section: Fabrication Of the Perovskite Solar Cellmentioning
confidence: 99%
“…However, it is found that the π-conjugated organic spacers currently used in 2D–3D heterostructured perovskites tend to result in concentration photoluminescence (PL) quenching, which is difficult to take full advantage of the splendid optical properties of π-conjugated organic spacers, hindering the effective sensitization process . Noteworthy, organic molecules with the aggregation-induced emission (AIE) property exhibit excellent PL emission behavior in the aggregated state due to the limitation of the intramolecular rotation, which have become the promising luminophores in PSCs. Chen et al employed a 3D AIE molecule, TPE–DPP 4 with the tetraphenylethylene (TPE) core and diketopyrrolopyrrole (DPP) arm, to fabricate CH 3 NH 3 PbI 3 (MAPbI 3 ) films. It is demonstrated that the TPE–DPP 4 can act as the light-absorber and meanwhile effectively improve film crystalline quality, as well as promote the charge transfer .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al have added tetra­(4-methoxyphenyl)­ethylene (TMOE) into the MAPbI 3 perovskite film to increase the radiative recombination ratio of free carriers to excitions . The Xiong group has introduced a donor–acceptor (D–A) type AIE molecule, tetraphenylethene-2-dicyano-methylene-3-cyano-4,5,5-trimethyl-2,5-dihydrofuran (TPE–TCF), into the perovskite film to regulate the crystal growth, reduce defects, and provide additional charge transfer channels . However, until now, these AIE molecules have mainly been applied as additives in PSCs, with less research on the construction of 2D–3D heterostructured perovskites via the employment of π-conjugated AIE organic spacers.…”
Section: Introductionmentioning
confidence: 99%